1969
DOI: 10.1126/science.166.3901.122
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonomycin, a New Antibiotic Produced by Strains of Streptomyces

Abstract: Phosphonomycin is a newly discovered antibiotic produced by streptomycetes. It is effective, when administered by the oral route, to mice infected with Gram-positive or Gram-negative microorganisms. The antibiotic is bactericidal and inhibits cell-wall synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
304
0
3

Year Published

1977
1977
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 554 publications
(314 citation statements)
references
References 7 publications
2
304
0
3
Order By: Relevance
“…1,2 It irreversibly inhibits MurA (UDP-N-acetylglucosamine-3-enolpyruvyltransferase), an important enzyme in bacterial cell wall biosynthesis (Scheme 1). 3 This inhibition is achieved through alkylation of an active-site cysteine residue, which performs a nucleophilic attack on the C2 atom of fosfomycin.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It irreversibly inhibits MurA (UDP-N-acetylglucosamine-3-enolpyruvyltransferase), an important enzyme in bacterial cell wall biosynthesis (Scheme 1). 3 This inhibition is achieved through alkylation of an active-site cysteine residue, which performs a nucleophilic attack on the C2 atom of fosfomycin.…”
Section: Introductionmentioning
confidence: 99%
“…Fosfomycin, originally isolated in 1969 as a product of Streptomyces spp. [1], could prove to be such an example. Several studies have shown that fosfomycin has retained substantial antimicrobial activity against 'problem'…”
Section: Introductionmentioning
confidence: 99%
“…1). Initially released by a few bacterial species, such as Streptomyces spp [26][27][28] or Pseudomonas syringae, 29 it is now produced synthetically for pharmaceutical purposes. The disodium salt is administered parenterally and the trometamine salt orally.…”
Section: Pharmacokinetics and Pharmacodynamics Descriptionmentioning
confidence: 99%